Bouncing off the balloon: A new trick for selective cystic duct cannulation. (26th May 2020) - Gulati, Rishabh; Rustagi, Tarun
Abstract : Selective cannulation of the cystic duct for endoscopic transpapillary gallbladder drainage can be challenging in cases with a caudally branching cystic duct. Gulati and Rustagi describe a novel and simple technique in which a guidewire is bounced off a stone extraction balloon and redirected into the cystic duct.